2019
DOI: 10.3174/ajnr.a6303
|View full text |Cite
|
Sign up to set email alerts
|

Automated ASPECTS in Acute Ischemic Stroke: A Comparative Analysis with CT Perfusion

Abstract: BACKGROUND AND PURPOSE: Automated ASPECTS has the potential of reducing interobserver variability in the determination of early ischemic changes. We aimed to assess the performance of an automated ASPECTS software against the assessment of a neuroradiologist in a comparative analysis with concurrent CTP-based CBV ASPECTS. MATERIALS AND METHODS: Patients with anterior circulation stroke who had baseline NCCT and CTP and underwent successful mechanical thrombectomy were included. NCCT-ASPECTS was assessed by 2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 37 publications
(48 reference statements)
5
34
2
Order By: Relevance
“…This study showed that there was no significant difference between the NCCT- and Auto-ASPECTS, which is consistent with previous studies [ 7 9 , 19 , 22 24 ]. Sundaram et al showed that the Auto-ASPECTS performed equally and the NCCT-ASPECTS in both the early and late time windows (≥ 6 or < 6 h) [ 19 ]. This shows that the Auto-ASPECTS has great potential in accelerating the evaluation of AIS patients, which could save time and reduce the burden of the doctors and may be widely applied in stroke centers at all levels.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that there was no significant difference between the NCCT- and Auto-ASPECTS, which is consistent with previous studies [ 7 9 , 19 , 22 24 ]. Sundaram et al showed that the Auto-ASPECTS performed equally and the NCCT-ASPECTS in both the early and late time windows (≥ 6 or < 6 h) [ 19 ]. This shows that the Auto-ASPECTS has great potential in accelerating the evaluation of AIS patients, which could save time and reduce the burden of the doctors and may be widely applied in stroke centers at all levels.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the scores of the CTP-ASPECTS method were significantly lower than those of the other two scoring methods. The median CTP-ASPECTS was 6, which was lower than the previously reported 8, which might be due to the relatively high proportion of ASPECTS < 6 in the present study (23/63 vs 6/58) [ 19 ]. Since CTP can provide quantitative parameters such as the volume of the infarct core and ischemic penumbra, the CTP-ASPECTS may better reflect the true status of ischemic territory than the NCCT-ASPECTS.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The baseline ASPECTS is a reliable predictor of the prognosis in patients with AIS [ 28 ]. ASPECTS has been included in the decision-making and assessment of neurovascular interventions in patients with AIS [ 3 ]. In the present study, we try to correlate ASPECTS with stroke subtypes, outcomes, and cognitive impairment in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…The ASPECTS was initially developed for the evaluation of the severity of early ischemic changes in cases with acute ischemic stroke (AIS) [ 3 ]. The ASPECTS evaluation has been increasingly involved in the choice of endovascular treatment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%